Analisis maslahah dalam millennium development goals - Bariyah, N. Oneng Nurul; Rohmah, Siti (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
The analysis of Maslahah in the Millennium Development Goals . This research is a study Maslahah of the Millennium Development Goals (MDGs). The focus of this research is Maslahahof five MDG targets, namely: 1) Reduction of extreme poverty and hunger, Equity in education, 3) Supporting the equation of gender and empowerment of women, 4) Reduce child mortality, 5) Improve maternal health The method of research used qualitative analysis. The data sources of this study is literature, Because this type of research is library research. The results Showed that the millennium goals are maslahah values that have an influence on the maintenance of maqasid al-Shariâah, namely: to maintain religion, mind, spirit, Ancestry, wealth, lineage. All of this indicates the existence of universal values of Islamic law as rahmatan lilâalamin and suitable for all times and places salih likulli zaman wa makan.